2000
DOI: 10.1055/s-2000-6498
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Reduction of Aldehydes in the Presence of Ketones Utilizing Raney Nickel

Abstract: Raney nickel is an effective reagent to achieve the chemoselective reduction of aldehydes in the presence of ketones, which takes place in high yield. Only highly hindered aldehydes do not undergo reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Chemical shifts are given on the δ scale in parts per million relative to signals of CHCl 3 as an internal standard (at 7.24 and 77.00 ppm, respectively). Signals in 13 C NMR spectra were assigned using the DEPT technique and comparison with spectra of known related compounds [3][4][5][6][11][12][13][14]. Specific rotation was measured in CHCl 3 on a Perkin-Elmer 241 polarimeter.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical shifts are given on the δ scale in parts per million relative to signals of CHCl 3 as an internal standard (at 7.24 and 77.00 ppm, respectively). Signals in 13 C NMR spectra were assigned using the DEPT technique and comparison with spectra of known related compounds [3][4][5][6][11][12][13][14]. Specific rotation was measured in CHCl 3 on a Perkin-Elmer 241 polarimeter.…”
Section: Methodsmentioning
confidence: 99%
“…The pathway is sterically hindered in both the dissociated and associated forms, although more so for the latter, and thus unlikely. Such selectivity has been observed for the addition of soft The final benzyl deprotection 15 was accomplished using LiAlH 4 in the presence of stoichiometric NiCl 2 , which after 11 h gave jaspaquinol 1 in 83% yield. The structure of 1 was confirmed by comparison with the natural product ( 1 H and 13 C NMR), which is identical and provides verification of the reported structure.…”
Section: Introductionmentioning
confidence: 93%
“…Reaction of 10 with arylstannane 12 15 in the presence of Pd 2 dba 3 AECHCl 3 and PPh 3 gave the S N 2 product 13 in 92% yield, whereas use of the bromide 11 gave the S N 2 product in a lower 81% yield.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…1,2 Our recent studies have revealed that this reagent may also be very effective in carrying out the chemoselective reduction of organic halides.…”
mentioning
confidence: 99%